Wybory edukacyjne mieszkańców miast = City inhabitants` educational choices - the case of Zielona Góra - Walentynowicz-Moryl, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Every city is a sphere in which schools competing for potential students are situated. The aim of this article is to specify which factors determine decisions concerning ity inhabitants` school choices. During the analysis of colleted empirial material, I intend to verify the hypothesis claiming that the area in a city where the school is situated has less and less influence on young people`s eduational choices.
Keywords: edukacja; miasto; mieszkańcy miast